2017
DOI: 10.1039/c7bm00294g
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of octadecylamine-functionalized nanodiamond on primary human macrophages

Abstract: Chronic inflammatory disorders such as rheumatoid arthritis are characterized by excessive pro-inflammatory or “M1” activation of macrophages, the primary cells of the innate immune system. Current treatments include delivery of glucocorticoids (e.g. dexamethasone – Dex), which reduce pro-inflammatory M1 behaviour in macrophages. However, these treatments have many off-target effects on cells other than macrophages, resulting in broad immunosuppression. To limit such side effects, drug-incorporated nano- and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 76 publications
(83 reference statements)
1
37
1
Order By: Relevance
“…Again, we observed that cells treated with high Dex microparticles acted similarly to the positive control cells treated with continuous Dex, even 7 days after microparticle administration. CD163 , a gene associated with hemoglobin and haptoglobin scavenging, and MERTK , a gene associated with apoptotic cell clearance, were differentially expressed across treatment conditions in macrophages on day 7. As expected, free Dex treatment increased the expression of CD163 and MERTK .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Again, we observed that cells treated with high Dex microparticles acted similarly to the positive control cells treated with continuous Dex, even 7 days after microparticle administration. CD163 , a gene associated with hemoglobin and haptoglobin scavenging, and MERTK , a gene associated with apoptotic cell clearance, were differentially expressed across treatment conditions in macrophages on day 7. As expected, free Dex treatment increased the expression of CD163 and MERTK .…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have attempted to harness the immune system through administration of immunomodulatory drugs or through biomaterial applications . Several landmark studies showed the possibility of using biomaterials to modulate macrophage phenotype and behavior for therapeutic applications . Here, we describe a novel strategy to use intracellular drug‐loaded microparticles to modulate macrophage gene expression for up to 7 days after microparticle administration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations